2006
DOI: 10.1007/s11096-005-4213-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potential Drug-related Problems in the Elderly: The Role of the Community Pharmacist

Abstract: In this vulnerable group of elderly patients potential DRPs frequently occur. Community pharmacists can play an important role in the identification, assessment and prevention of potential DRPs in the elderly. It is useful to investigate which part of potential DRPs can be avoided by the intervention of the community pharmacist in collaboration with the prescriber and the patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
45
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 31 publications
6
45
0
4
Order By: Relevance
“…The simplest model defines polypharmacy as the use of ‡2 medications [11]. In contrast, many relevant works define polypharmacy as the prescription of ‡6 drugs [12,[18][19][20]. In our study, we used the latter threshold.…”
Section: Discussionmentioning
confidence: 99%
“…The simplest model defines polypharmacy as the use of ‡2 medications [11]. In contrast, many relevant works define polypharmacy as the prescription of ‡6 drugs [12,[18][19][20]. In our study, we used the latter threshold.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies [106,107] have shown that pharmacists can help to assess and prevent potential drug-related problems, but further data are necessary.…”
Section: Polypharmacy Compliance and Drug Averse Events In The Elderlymentioning
confidence: 99%
“…Pharmacists, as drug experts, should take up their responsibility of detecting and preventing DRPs, if they wish to claim a role in DRP assessment. 30 The increased knowledge following the interactive CE course did not appear to have a long-lasting effect. The follow-up survey revealed that pharmacists did not remember much of the CE course.…”
Section: Discussionmentioning
confidence: 90%